The Econometrics of Energy Systems 2007
DOI: 10.1057/9780230626317_11
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vertical Integration and Horizontal Diversification on the Value of Energy Firms

Abstract: We analyze the long-run return performance of 27 value-weighted equity portfolios based on a classification of the US energy sector that follows traditional industrial organization categories. When adjusted to market and fuel risks, portfolio returns show that both vertical integration and horizontal diversification failed to produce shareholder value during the 1990-2003 period. This confirms the theoretical predictions of both financial economics and industrial organization and shows that the wave of corpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In their study, Pozzi and Vassilopoulos (2007) analyze the long-run return performance of 27 value-weighted equity portfolios based on a classification of the US energy sector that follows traditional industrial organization categories. When adjusted to market and fuel risks, portfolio returns show that both backward vertical integration and horizontal diversification failed to produce shareholder value during the 1990-2003 period.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…In their study, Pozzi and Vassilopoulos (2007) analyze the long-run return performance of 27 value-weighted equity portfolios based on a classification of the US energy sector that follows traditional industrial organization categories. When adjusted to market and fuel risks, portfolio returns show that both backward vertical integration and horizontal diversification failed to produce shareholder value during the 1990-2003 period.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The choice of a mean-variance criterion is often chosen for its tractability at the expense of its realism. Presently, the scientific literature already has several works on the application of Markowitz's optimum portfolio theory to energy mix [42,24,25], as well as studies on the relationship between the corporate structure of the electricity sector and their stock market valuation [40] or economies of scale obtained by vertical integration from an econometric point of view [26] or from a partial equilibrium point of view [1].…”
Section: Quantitative Models To Assess Utilities Business Model Boundsmentioning
confidence: 99%
“…For example, in newspaper and television media industries, firms tend to be almost fully integrated and they currently shifted outside the stages of production along with the emergence of strong intermediate markets (Gambaro, 2005). However, in the energy sector in the United States, the effects of integration produced little return performance for all energy firms, particularly natural gas industry (Pozzi and Vassilopoulos, 2007). For the food and agricultural sectors, it has been observed that large processing firms have a premium associated with integration due to lower fixed costs, lower variable costs, and better abilities for negotiation (Dorsey and Boland, 2009).…”
Section: Introductionmentioning
confidence: 99%